2016
DOI: 10.11604/pamj.supp.2016.25.1.6169
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing utilization of intermittent preventive treatment for pregnancy in the Gushegu district, Ghana, 2013

Abstract: IntroductionThe coverage of adequate (≥2 doses) IPTp-SP in Ghana is below the national target of 80% and that is a threat to reducing the incidence of malaria in pregnancy. The primary objective of the study was to determine the client and facility related factors associated with adequate uptake of IPTp-SP and suggest approaches for increased uptake.MethodsA cross sectional study was conducted among ANC clients and staff in Gushegu, questionnaires was administered to 330 conveniently sampled nursing mothers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 9 publications
4
22
1
Order By: Relevance
“…Compared with other studies [ 23 , 25 , 26 , 33 , 38 ], this study further demonstrated the independent association between timing of the first ANC visit, in addition to the number of ANC visits, and IPTp uptake among pregnant women. In particular, the results suggest that reporting for the first ANC earlier during pregnancy, despite having an inadequate number of ANC visits, was associated with recommended IPTp uptake.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Compared with other studies [ 23 , 25 , 26 , 33 , 38 ], this study further demonstrated the independent association between timing of the first ANC visit, in addition to the number of ANC visits, and IPTp uptake among pregnant women. In particular, the results suggest that reporting for the first ANC earlier during pregnancy, despite having an inadequate number of ANC visits, was associated with recommended IPTp uptake.…”
Section: Discussionsupporting
confidence: 51%
“…Increased odds of recommended IPTp uptake in those with adequate visits despite having late initiation of ANC were also observed, but with a wider confidence interval, possibly because of the smaller sample number in this category. Two Ghanaian studies reported that 4 or more ANC visits were associated with higher IPTp uptake [ 26 , 33 ]. The current findings further revealed the significance of this factor, independent of the timing of the first ANC visit, suggesting the need for healthcare workers to encourage late ANC initiators to make frequent ANC visits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FETPs play critical roles in addressing priority public health problems in countries, often with the collaboration and support of international initiatives such as the US President’s Emergency Plan for AIDS Relief ( 37 , 38 ), the President’s Malaria Initiative ( 39 , 40 ), and the Global Polio Eradication Initiative ( 41 , 42 ). This approach ensures that residents’ work supports national and global priorities while the residents practice applying epidemiologic methods to these programs and providing public health service.…”
Section: Outcomes and Effects Of Fetpsmentioning
confidence: 99%